2020
DOI: 10.15560/16.4.1055
|View full text |Cite
|
Sign up to set email alerts
|

First report of Penicillium brasilianum Bat., P. cluniae Quintan., and P. echinulonalgiovense S. Abe ex Houbraken & R.N. Barbosa (Eurotiales, Aspergillaceae) as endophytes from a bromeliad in the Caatinga dry forest in Brazil

Abstract: Penicillium brasilianum Bat., P. cluniae Quintan., and P. echinulonalgiovense S. Abe ex Houbraken & R.N. Barbosa are reported for the first time as endophytes from the leaves of an endemic bromeliad in the Caatinga dry forest in Brazil. For species determination, phenotypic features were analysed along with the sequencing of the β-tubulin and calmodulin genes. Penicillium Link isolates obtained in this study showed the typical morphology of species in the Lanata-Divaricata section. These resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, based on the culture morphology and microstructure properties and compared to previous studies which described the fungal species [57,58], the fungal strain was identified as A. aculeatus EAN506. P. pedernalense EAN604 shows the highest homology with P. mariae-crucis, P. brasilianum, P. simplicissimum, P. pulvillorum, and T. biappendiculata (Figure 11) However, T. biappendiculata was totally excluded since it has different spore morphology [59]; P. brasilianum was excluded based on the culture morphology reported by Freire et al [60]; while P. pulvillorum was excluded based on the spore's morphology as reported by Mansouri et al [61]. Together with the morphological characteristics in comparison with Laich and Andrade [36], the fungal strain was recognized as P. pedernalense EAN604.…”
Section: Molecular Characteristics Of Fungal Isolates From Peat Soilmentioning
confidence: 99%
“…However, based on the culture morphology and microstructure properties and compared to previous studies which described the fungal species [57,58], the fungal strain was identified as A. aculeatus EAN506. P. pedernalense EAN604 shows the highest homology with P. mariae-crucis, P. brasilianum, P. simplicissimum, P. pulvillorum, and T. biappendiculata (Figure 11) However, T. biappendiculata was totally excluded since it has different spore morphology [59]; P. brasilianum was excluded based on the culture morphology reported by Freire et al [60]; while P. pulvillorum was excluded based on the spore's morphology as reported by Mansouri et al [61]. Together with the morphological characteristics in comparison with Laich and Andrade [36], the fungal strain was recognized as P. pedernalense EAN604.…”
Section: Molecular Characteristics Of Fungal Isolates From Peat Soilmentioning
confidence: 99%